Dendritic cell-specific transmembrane protein is required for synovitis and bone resorption in inflammatory arthritis - Garcia-Hernandez, Maria de la Luz; Rangel-Moreno, Javier; Garcia-Castaneda, Maricela; Kenney, H. Mark; Paine, Ananta; Thullen, Michael; Anandarajah, Allen P.; Schwarz, Edward M.; Dirksen, Robert T.; Ritchlin, Christopher T. (Frontiers in Immunology, 2022)
Abstract Objective. Dendritic Cell-Specific Transmembrane Protein (DC-STAMP) is essential for the formation of fully functional multinucleated osteoclasts. DC-STAMP deficient mice, under physiological conditions, exhibit osteopetrosis and develop systemic autoimmunity with age. However, the function of DC-STAMP in inflammation is currently unknown. We examined whether genetic ablation of DC-STAMP attenuates synovitis and bone erosion in TNF transgenic (Tg) and K/BxN serum-induced murine rheumatoid arthritis. Methods. We evaluated arthritis onset in Tg(hTNF) mice lacking DC-STAMP and 50:50 chimeric mice by visual examination, measurement of ankle width, micro-CT-scan analysis and quantitation of the area occupied by osteoclasts in bone sections. To further investigate the cellular and molecular events modulated by DC-STAMP, we measured serum cytokines, determined changes in cytokine mRNA expression by monocytes activated with IL4 or LPS/IFNγ and enumerated immune cells in inflamed mouse joints. Results. Synovitis, bone loss and matrix destruction are markedly reduced in Dcstamp-/-;Tg(hTNF) mice. These mice had significantly lower CCL2 and murine TNF serum levels and exhibited impaired monocyte joint migration compared to Tg(hTNF) mice. The reduced arthritic severity in Dcstamp deficient mice was associated with compromised monocyte chemotaxis, cytokine production, and M2 polarization. Conclusion. These results reveal that DC-STAMP modulates both bone resorption and inflammation and may serve as an activity biomarker and therapeutic target in inflammatory arthritis and metabolic bone disease.